A comparison of the channel geomorphic unit composition of regulated and unregulated reaches in the Soča river - Maddock, Ian; Smolar Žvanut, Nataša; Hill, Graham (Journal for Geography, 2007)
This paper examines the effects of flow regulation on the size, spatial distribution and connectivity of channel geomorphic units (CGU) in the Soča River, Slovenia. A river channel survey was completed along three reaches, i.e. an unregulated reach (reach 1), and two regulated reaches with lower discharges, (reach 2 and 3). Results demonstrated significant differences in the CGU composition between the unregulated and regulated reaches. Flow regulation in the Soča River alters the dominant types of CGU’s present, significantly reduces the size of CGU’s, and affects the longitudinal distribution of types by reducing habitat connectivity and creating greater habitat fragmentation.
Keywords: Soča River; river regulation; habitat mapping; channel geomorphic unit; river hydraulics; river morphology